Performance Comparison of ECG Bio-Amplifier Between Single and Bi-Polar Supply Using Spectrum Analysis Based on Fast Fourier Transform - Anita Miftahul Maghfiroh; Syevana Dita Musvika; Vugar Abdullayev (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Heart performance is one of the vital signs that cannot be ignored and must be monitored periodically. In this case, the measuring range of the human heart rate is between 60-100 BPM, in which the measurement unit is expressed as Beat per Minute (BPM). Therefore, it is very important to use Electrocardiograph equipment to tap the electrical signals of the heart with correct readings and minimal interference such as frequency of electric lines and noise. The purpose of this study was to compare the instrumentation amplifier using a single supply with a bi-polar supply in the ECG design to select the best instrumentation amplifier, which is expected to contribute to other researchers in choosing the right type of instrumentation amplifier that is efficient and qualified. In this case, the research was carried out by comparing two single supply instrumentation amplifiers using the AD623 IC and the bi-polar supply using the AD620 IC, continued by the use of Fast Fourier Transform (FFT) to determine the frequency spectrum of the ECG signal. The test results further showed that the use of single power instrumentation could reduce more noise compared to the Bi-Polar instrumentation amplifier by strengthening 60 dB Low pass filter circuit. Meanwhile, the FFT results in finding the frequency spectrum explained that the FFT results on the ECG signal provided information that the ECG signal had a frequency range between 0.05 Hz and 100 Hz. When the frequency is more than 100 Hz, the frequency started to be suppressed and when the frequency is less than 100 Hz, the frequency is passed. This research could be further used as a reference by other researchers to determine which type of instrumentation amplifier is better.